From Dogma to Dialogue: Reframing Islamic Religious Education through Dialogic Pedagogy in Indonesian Madrasah Aliyah - Alam, Ahmad Sirojul; Fadlillah; Muhyiddin, Muhammad Robet (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
This study examines how Islamic Religious Education teachers in Indonesian Madrasah Aliyah transition from dogmatic, memorization-oriented instruction to dialogic and inquiry-based pedagogy in response to growing demands for critical thinking in faith-based education. Addressing the limited empirical evidence on dialogic pedagogy in Islamic secondary education, this qualitative case study draws on classroom observations, semi-structured interviews, and document analysis involving six teachers, eighteen students, and school administrators. Findings show that teachers integrate rational–critical reasoning and Problem-Based Learning (PBL) to connect classical Islamic principles with contemporary social issues, resulting in increased student motivation, active participation, and analytical engagement. Although constrained by limited institutional resources and professional training, these dialogic practices foster deeper conceptual understanding while simultaneously strengthening students’ spiritual reflection. The study contributes to the discourse on Islamic critical pedagogy by empirically demonstrating that religious commitment and critical inquiry are not oppositional but mutually reinforcing within classroom practice. It purposes an empirically grounded model for reforming Islamic education through reflective and dialogic teaching, offering practical implications for educators and policymakers seeking to bridge religious tradition with the demands of contemporary education.